2013
DOI: 10.1108/14777831311303100
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of environmental management system performance in the Algerian companies certified ISO 14001

Abstract: Purpose -The purpose of this paper is to provide an immediate image about the reality of the Environmental Management System (EMS), as experienced by Algerian companies certified to ISO 14001. Design/methodology/approach -The adopted approach focused on the evaluation of different elements concerning the requirement of the reference ISO 14001, by the audit which constitutes the appropriate tool for the evaluation of such a system of management. Findings -The evaluation of different elements concerning the requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
(15 reference statements)
1
8
0
3
Order By: Relevance
“…Thus, this leads to better and higher firm's environmental performance. However, some problems were encountered: employees reluctant to follow procedures, the lack of knowledge, including problems with the adoption of the new regulation (Hariz & Bahmed 2013) (2003); Marshall and Mayer (1992) claimed that EMS training has a relationship to environmental performance whilst Hariz and Bahmed (2013) suggested that management commitment and support for EMS training has a relationship to environmental performance. Further study by Cole, Elliott and Strobl (2008) on firms in Ghana found that environmental training has positive influences on the firms' environmental performance.…”
Section: Environmental Trainingmentioning
confidence: 99%
“…Thus, this leads to better and higher firm's environmental performance. However, some problems were encountered: employees reluctant to follow procedures, the lack of knowledge, including problems with the adoption of the new regulation (Hariz & Bahmed 2013) (2003); Marshall and Mayer (1992) claimed that EMS training has a relationship to environmental performance whilst Hariz and Bahmed (2013) suggested that management commitment and support for EMS training has a relationship to environmental performance. Further study by Cole, Elliott and Strobl (2008) on firms in Ghana found that environmental training has positive influences on the firms' environmental performance.…”
Section: Environmental Trainingmentioning
confidence: 99%
“…One of the key matter in using EMS ISO14001 is it provides value-based thinking among companies, not to mentioned the sustainability value [11]. On that note, studies have proved that developing a pattern to design a sustainability supply chain based on several requirements, including ISO 14001 [13]; providing an immediate image about the reality of the EMS as experienced by Algerian certified ISO 14001 companies [14]; and the effect of ISO 14001 on environmental regulatory compliance in China [15] are some of the benefits of adopting EMS 14001.…”
Section: Results and Discussion Environmental Management System (Ems)mentioning
confidence: 99%
“…The main stream of literature focused examining the drivers for green purchase adoption among EMS 14001 certified companies in Malaysia ElTayeb et al, [9] perceived benefits derived from ISO14001 registrations for firms in a newly industrialized country like Malaysia [10]; linking the adoption of an EMS ISO14001 with valuebased thinking and sustainability [11] describing the underlying structure of the ISO 14001 motives, difficulties and benefits and determining the respective latent constructs [12]; investigating how a group of companies have developed a pattern to design a sustainability supply chain based on several requirements, including ISO 14001 [13]; providing an immediate image about the reality of the EMS as experienced by Algerian certified ISO 14001 companies [14]; and the effect of ISO 14001 on environmental regulatory compliance in China [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…KFS for ISO 14001 certification have rarely been examined thoroughly in the literature [5]. Several studies have been conducted in emerging [9] and Middle-Eastern countries [10][11][12], but there are no studies from Arab Gulf countries. Fourth, there is a critical lack of research on comparing EMS certification in private and public organizations [6].…”
Section: Introductionmentioning
confidence: 99%